Possibilities of Using Webinars in the Training of Forensic Experts - Kozhevnikov, Valerii (Archives of Criminology and Forensic Sciences, 2022)
The research paper is devoted to the study of the possibility of implementing information technologies for training and improving the qualifications of forensic experts on the example of using webinars as one of the forms of distance learning. The main forms of conducting webinars, which can be used for the training of forensic experts, are presented. Requirements for conducting webinars in the system of training forensic experts were analyzed and their main strategies were identified. According to the results of the presented material, the advantages of using webinars for the training of forensic experts, and the wider implementation of information technologies in the educational process have been determined.